USAHA PENINGKATAN PRESTASI MELALUI PENGAWASAN DAN KOMUNIKASI KEPALA SEKOLAH TERHADAP GURU-GURU DI SD NEGERI 164521 KOTA TEBING TINGGI TAHUN PELAJARAN 2018/2019 - Emi Derita (FIP Unimed, 2019)
ABSTRACT The study was conducted at 164521 Public Elementary School in Tebing Tinggi, 2018/2019 Academic Year, September to November 2018. The population was elementary school teachers in 164521 Public Elementary School Tebing Tinggi, 2018/2019 Academic Year with a population and a sample of 10 people. The purpose of the study was 1) to find out the benefits of the principal's supervision of the teacher's work performance. 2) knowing the form of headmaster's communication with the teachers. The results found that 1) there was a relationship between the principal's supervision and the work performance of 164521 Public Elementary School teachers in Tebing Tinggi which was significant between school principals' supervision and communication behavior with 164521 Public Elementary School teacher work performance Tebing Tinggi City.Keywords: Achievement, Supervision Communication ABSTRAK Penelitian dilaksanakan di SD Negeri 164521 Kota Tebing Tinggi Tahun Pelajaran 2018/2019 periode bulan September s/d November 2018. Populasi penelitian guru-guru SD di SD Negeri 164521 Kota Tebing Tinggi Tahun Pelajaran 2018/2019 dengan populasi dan sampel 10 orang. Tujuan penelitian adalah 1) untuk mengetahui manfaat pengawasan kepala sekolah terhadap prestasi kerja guru. 2) mengetahui bentuk komunikasi kepala sekolah terhadap guru-guru.Hasil penelitian menemukan bahwa 1) terdapat hubungan antara pengawasan kepala sekolah dengan prestasi kerja guru SD Negeri 164521 Kota Tebing Tinggi yang signifikan antara pengawasan dan prilaku komunikasi kepala sekolah dengan prestasi kerja guru SD Negeri 164521 Kota Tebing Tinggi.Kata Kunci : Prestasi , Pengawasan, Komunikasi